Novel VPS13A Gene Mutations Identified in Patients Diagnosed with Chorea-acanthocytosis (ChAc): Case Presentation and Literature Review - Shen, Yan; Liu, Xiaoming; Long, Xi; Han, Chao; Wan, Fang; Fan, Wenliang; Guo, Xingfang; Ma, Kai; Guo, Shiyi; Wang, Luxi; Xia, Yun; Liu, Ling; et al. (Frontiers in Aging Neuroscience, 2017)
Chorea-acanthocytosis (ChAc) is a rare autosomal recessive inherited syndrome characterized by hyperkinetic movements, seizures, cognitive impairment, neuropsychiatric symptoms, elevated serum biochemical indicators and acanthocytes detection in peripheral blood smear. Vacuolar protein sorting 13A (VPS13A) gene mutations have been proven to be genetically responsible for the pathogenesis of ChAc. Herein, based on the typical clinical symptoms and neuroimaging features, we present two suspected ChAc cases which are further genetically confirmed by four novel VPS13A gene mutations. Nevertheless, the sharp contrast between the population base and published ChAc reports implies that ChAc is considerably underdiagnosed in China. Therefore, we conclude several suggestive features and propose a diagnostic path of ChAc from a clinical, genetic and neuroimaging perspective, aiming to facilitate the diagnosis and management of ChAc in China.